Sosialisasi dan Pendampingan Metode 5S untuk Meningkatkan Keteraturan dan Produktivitas di PT Fanah Jaya Maindo - Cipto Purwanto; M. Ibrahim Ats-Tsauri; Annisa Syahliantina; Ghina Farhah Azizah; Christa Dian Pratiwi (Jurnal Pelita Pengabdian, 2026)
The objective of this community service activity was to determine the extent to which employees understand the company’s system for implementing the 5S concept, to identify problems in the application of 5S during work processes, and to establish appropriate control measures and follow-up actions for 5S implementation at PT Fanah Jaya Maindo. The method used in this activity was the 5S method, which is a technique for maintaining the quality of the work environment by enhancing orderliness, creating a safe and comfortable workplace, and improving efficiency and productivity. Participants in this activity consisted of all staff and supervisory employees working at PT FJM. Based on observation results, the problem identified in the implementation of 5S was the suboptimal application of the Seiketsu (standardization) principle. This issue indicates the need for a more structured system of tool coding and an obligation for each employee to return work equipment to its original place after use. The results of the socialization activity showed that participants gained a very good understanding of the material presented. Positive participant responses were reflected in the appreciation expressed toward both the content and the manner in which the activities were delivered. This achievement of understanding is expected to encourage an increased commitment among employees to apply the 5S principles consistently in their respective work environments